Diffusion of fructose in water: a molecular dynamics study - Bhusal, Santosh; Pantha, Nurapati (Himalayan Physics, 2020)
Present work carries the molecular dynamics (MD) simulation to study the self-diffusion coefficients of fructose (C6H12O6) and SPC/E (Extended Simple Point Charge) water (H2O) along with their binary diffusion coefficients at different temperature (298.15 K, 303.15 K, 308.15 K and 312.15 K). A dilute solution of 3 molecules of fructose (solute, mole fraction 0.0018) and 1624 molecules of water (solvent, mole fraction 0.9982) has been taken for making it relevant to the previously reported experiment. The structural analysis of the mixture has been estimated by using the radial distribution function (RDF) of its constituents. Mean square displacement (MSD) and Einstein’s relation have been used to ﬁnd the self-diffusion coefficients of both the solute and solvent. Furthermore, Darken’s relation ﬁnds the binary diffusion coefficients. The temperature dependence of diffusion coefficients follows the Arrhenius behavior which further calculates activation energy of diffusion. The results from the present work agree well with the previously reported experimental values.